Organic Farming Concept and advantages - Singh, Tej Pal; Singh, Ranbir; Shivani, Shivani (Indian Farming, 2015)
Organic farming implies growing of agricultural and horticultural crops without chemical fertilizer, herbicide and pesticides. Agricultural practices followed in organic farming are governed by the principles of ecology and are within the ecological means.